Visions of sustainable development and the future of smallholder farmers in sub-Saharan Africa (and beyond) - Boda, Chad S.; Akorsu, Angela Dziedzom; Armah, Frederick Ato; Atwiine, Adrine; Byaruhanga, Ronald; Chambati, Walter; Ekumah, Bernard; Faran, Turaj; Hombey, Charles Tetteh; Isgren, Ellinor; Jerneck, Anne; Mazwi, Freedom; et al. (Frontiers in Sustainable Food Systems, 2024)
Smallholder farmers are widely touted as essential to sustainable agricultural development in sub-Saharan Africa and beyond. But what exactly is meant by sustainable development, and how are smallholder farmers expected to contribute to it? In this perspective, we describe and assess two competing visions of sustainable development, namely Capital Theory and the Capabilities approach, paying special attention to the major yet divergent repercussions each approach implies for the future of smallholder farmers and the activities of their representative organizations. We present the core concepts, tools and practices stemming from each sustainable development perspective, and from a critique of these motivate the superiority of a capabilities approach as more conducive to smallholder farmers wellbeing now and in the future. In doing so, we bring to the fore the pivotal role smallholder farmer organizations and rural social movements, as collective vehicles for smallholder political